Financing Universal Health Care: Premiums or Payroll Taxes? - Maria Feldman; Hans Fehr (ZBW - Leibniz Information Centre for Economics, 2021)
This paper presents an overlapping generations model where agents face labor-income and health risks in order to quantify the macroeconomic and welfare consequences of reform options for the German health insurance system. In addition to labor supply, consumption and savings, households also choose health expenditures in order to improve the health status and longevity. Starting from an initial equilibrium which reflects the current public and private mixture of the German health insurance system, we simulate the transition towards a uniform system with either funded or unfunded premiums or payroll taxes. The former have favorable labor supply effects, while the latter provide an implicit insurance device against income shocks. Our simulations indicate that even with modest risk aversion the insurance property of payroll taxes may compensate their negative impact on labor supply. Consequently, the economic benefits of health premium models versus the citizen insurance models may have been overstated in the past. We also show that individual health expenditures may have significant welfare effects, but they do not change our conclusions qualitatively.
Keywords: C68; D91; H55; J24; 330; stochastic general equilibrium; overlapping generations; endogenous health